Energy Assessment of A Pcm–Embedded Plaster: Embodied Energy Versus Operational Energy. (November 2015) - Carbonaro, Corrado; Cascone, Ylenia; Fantucci, Stefano; Serra, Valentina; Perino, Marco; Dutto, Marco
Abstract: Phase change materials (PCMs) are an emerging technology that can be integrated in building envelope components. PCMs are able to stabilise indoor air temperature and increase thermal energy storage especially in lightweight constructions. Within a research activity aimed at developing advanced plasters with improved thermal properties, a plaster which incorporates a microencapsulated paraffin-based PCM was developed. The paper highlights the importance of an overall analysis, facing both operational and embodied energy, since the expected decrease of the energy consumption during the operational stage difficultly counterbalances the high energy impact related to manufacturing processes.